LEGIBILITY ANALYSIS ELEMEN PEMBENTUK CITRA KOTA DI KAWASAN PASAR SUDIMAMPIR KOTA BANJARMASIN - Muhammad Alif Hafizhan Naufal; Nadia Almira Jordan (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2022)
Sudimampir Market is in the Central Business District (CBD) area of ​​Banjarmasin City, South Kalimantan Province, which was initiated by a Dutch architect, Ir. Thomas Karsten in 1937. Around the 1960s this market began to grow rapidly because many foreign traders started trading around the area. The Sudimampir Market area is one of the oldest service trading areas in Banjarmasin City but does not show any distinct image physically that represents it as an old town area that can increase the number of visitors and can add value ​​to an area. The problem raised in this study is what are the characteristics of the five elements of city image in the Sudimampir Market Area that contribute to the image formation of the area as a whole. This study used Legibility Analysis to see the characteristics and legibility of the five elements of the city's image in the Sudimampir Market Area. The results showed that there were 3 path elements with characteristics that need to be improved and 3 path elements with invisible characteristics, 1 edge element, 1 district element, 9 intersection nodes elements and 3 activity nodes elements, and 1 landmark element. City image elements that describe the Sudimampir Market Area as the Old Town Area are the path and the district, while other elements do not enough describe the Sudimampir Market Area as the Old City Area of Banjarmasin.